Dark Angel : A Letty Davenport Novel - Sandford, John, 1944 February 23- (New York : G.P. Putnam's Sons, 2023)
"Letty Davenport's days working a desk job are behind her. Her previous actions at a gunfight in Texas--and her incredible skills with firearms--draw the attention of several branches of the US government, and make her a perfect fit for even more dangerous work. The Department of Homeland Security and the NSA have tasked her with infiltrating a hacker group, known only as Ordinary People, that is intent on wreaking havoc. Letty and her reluctant partner from the NSA pose as free-spirited programmers for hire and embark on a cross country road trip to the group's California headquarters"--
Keywords: Undercover operations -- Fiction; Computer crimes -- Fiction; California -- Fiction; Thrillers (Fiction); Novels